الإعلانات التلفزيونية وأثرها في سلوك المستهلك دراسة ميدانية على عينة من طلاب الجامعة الدولية الخاصة للعلوم والتكنولوجيا - شاهين, عزت; زوبته, حلا (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
تهدف هذه الدراسة إلى معرفة مدى تأثير الإعلانات التلفزيونية على السلوك الشرائي للشباب الجامعي، وإلى رصد مدى اهتمامهم في متابعة الإعلانات وبالتالي مدى تأثرهم بها، إضافة إلى نوعية تلك الإعلانات ومدى تصديقهم لها، ومعرفة هل قرار الشراء مرتبط بمتابعة الإعلان أم لا؟ فالإعلانات التلفزيونية تعد واحدة من أهم فروع الإعلان في الوقت الحاضر. دفع التطور التقني في وسائل التصوير والإضاءة والاتصالات باتجاه تطور شكل وأسلوب إنتاج الإعلان التليفزيوني، من حيث تصنيفه، وطريقة تنفيذه، ومؤثراته البصرية والسمعية, والذي أصبح له تأثيره النفسي الفعال على المتلقي، وبالتالي تأثير ذلك على قراره الشرائي، لقد أصبح الاعتماد على الدعاية والإعلان لتسويق البضائع والخدمات وحتى الأفكار أمراً لا يمكن الاستغناء عنه .This study aimed to determine the effect of advertising on the purchasing behavior of the university youth and to monitor the extent of their interest in follow-up ads and the extent of its influence in addition to the quality of those ads and how they believe it s and to know whether their purchase decision is related to the ads seeing or not? television advertisements is one of the most important ways of advertising in the present time, with the technological development in photography ,lighting, and communications; a combined development occurred with the format and style of the production of TV advertising, concerning its classification, method of implementation, the effects used visually and acoustically . it now has its effective psychological impact on the receiver in different countries via satellites. Depending on advertising for marketing of goods, services, and even ideas is irreplaceable nowadays.